PENGARUH STRUKTUR GOOD CORPORATE GOVERNANCE DAN KINERJA LINGKUNGAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (Studi Pada Perusahaan Manufaktur di Bursa Efek Indonesia Periode 2011-2015) - Anna Sukasih; Eko Sugiyanto (Riset Akuntansi dan Keuangan Indonesia, 2017)
The aim of this research is to analysis the influence of managerial ownership, institutional ownership, audit committee, size of board of commissioners, and environmental performance on the disclosure of Corporate Social Responsibility (CSR). The measurement of corporate social responsibility based on the Global Reporting Initiative disclosure index (GRI) 2013 as seen from the company’s annual report. The population of this research is manufacture companies listed in Indonesia Stock Exchange (IDK) 2011-2015. Research sampling used purposive sampling technique and found 24 companies, with 5 years of observation. So, the total sample studied was 120. The collected data was analysis using classic assumption test then do hypothesis test. Testing the hypothesis in this study using multiple regression analysis with t-test, f, and coefficient of determination. The result indicate that managerial ownership and institutional ownership have a significant influence on the disclosure of Corporate Social Responsibility (CSR). Meanwhile, audit committee, size of board of commissioners, and environmental performance don’t have significant influence on the disclosure of Corporate Social Responsibility (CSR). Keywords: Corporate Social Responsibility (CSR), managerial ownership, institutional ownership, audit committee, size of board of commissioners, and environmental performance.